Quantum-chemical properties of diclofenac - Syrovaya А. О.; Chekman, I. S.; Levashova, O. L.; Kozub, S. M. (Reports of the National Academy of Sciences of Ukraine, 2016)
Diclofenac sodium is a nonsteroidal antiinflammatory drug, which is widely used in medical practice. The studies of quantum-chemical properties of diclofenac are carried out. An optimization of the molecular geometry is made by the means of the PM3 method and Polak – Ribiere algorithm. The atomic charges, total dipole moment of the molecule, and characteristics of molecular orbitals are determined. The negative electrostatic potential of diclofenac is on oxygen and nitrogen atoms. Diclofenac is a soft reagent according to the HOMO-LUMO gap. The established quantum-chemical properties of diclofenac may become a basis of its molecular mechanisms of pharmacological action.